2022
DOI: 10.3390/ijms23158546
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Somatic Genetic Alterations in Circulating Cell-Free DNA/RNA of Patients with “Oncogene-Addicted” Advanced Lung Adenocarcinoma: A Real-World Clinical Study

Abstract: Liquid biopsy has advantages over tissue biopsy, but also some technical limitations that hinder its wide use in clinical applications. In this study, we aimed to evaluate the usefulness of liquid biopsy for the clinical management of patients with advanced-stage oncogene-addicted non-small-cell lung adenocarcinomas. The investigation was conducted on a series of cases—641 plasma samples from 57 patients—collected in a prospective consecutive manner, which allowed us to assess the benefits and limitations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…57 However, recent lines of evidence suggest potential utilisation of liquid biopsy for gene fusions, including those occurring in NTRK genes. 58 Pan-cancer studies reported a higher than 85% concordance between tissue and plasma in detecting NTRK fusions, suggesting the feasibility of this analysis through ctDNA testing. 59,60 Nevertheless, in a series of patients with lung cancer, Hasegawa and colleagues investigated the analytical validity and clinical usefulness of fusion detection through circulating cell-free RNA (cfRNA) analysis showing its higher sensitivity compared with ctDNA.…”
Section: Ntrk Fusionsmentioning
confidence: 97%
See 1 more Smart Citation
“…57 However, recent lines of evidence suggest potential utilisation of liquid biopsy for gene fusions, including those occurring in NTRK genes. 58 Pan-cancer studies reported a higher than 85% concordance between tissue and plasma in detecting NTRK fusions, suggesting the feasibility of this analysis through ctDNA testing. 59,60 Nevertheless, in a series of patients with lung cancer, Hasegawa and colleagues investigated the analytical validity and clinical usefulness of fusion detection through circulating cell-free RNA (cfRNA) analysis showing its higher sensitivity compared with ctDNA.…”
Section: Ntrk Fusionsmentioning
confidence: 97%
“…In 2019, a strategy for the most appropriate implementation according to samples availability was proposed by the European Society for Medical Oncology's Translational Research and Precision Medicine Working Group 57 . However, recent lines of evidence suggest potential utilisation of liquid biopsy for gene fusions, including those occurring in NTRK genes 58 . Pan‐cancer studies reported a higher than 85% concordance between tissue and plasma in detecting NTRK fusions, suggesting the feasibility of this analysis through ctDNA testing 59,60 .…”
Section: Applications Of Ctdna Analysis In Metastatic Breast Cancermentioning
confidence: 99%
“…Detecting gene alterations in cell-free circulating DNA/RNA via liquid biopsy may also be considered a helpful approach to integrate with conventional diagnostic and thera-peutic programs. In their study, Lupini et al investigated the importance of liquid biopsy in the clinical management of patients with NSCLC by using next-generation sequencing (NGS) and assessed whether or not this method could also be applied at earlier stages of the disease, including the first diagnosis [26]. The results obtained from 641 plasma samples of 57 patients allowed the detection of mutations in circulating DNA/RNA 80 days prior to disease progression, including 13 de novo mutations [26].…”
mentioning
confidence: 99%
“…In their study, Lupini et al investigated the importance of liquid biopsy in the clinical management of patients with NSCLC by using next-generation sequencing (NGS) and assessed whether or not this method could also be applied at earlier stages of the disease, including the first diagnosis [26]. The results obtained from 641 plasma samples of 57 patients allowed the detection of mutations in circulating DNA/RNA 80 days prior to disease progression, including 13 de novo mutations [26]. However, the low amount of circulating DNA/RNA at the early stage of the disease severely limits the usefulness of this method of analysis for these subjects, although the sensitivity of this method is improving over time.…”
mentioning
confidence: 99%